Genetics, health and society - Perry, Brea L. (Advances in medical sociology ;, 2015)
Gene-environment interactions and epigenetics are often conceptualized as key mechanisms underlying the influence of social status and social interaction on the distribution of health and illness in society. At the same time, genetic technologies, research, and explanations for health and behavior have rapidly infiltrated popular culture. Genetic information and treatments tailored to individual genomes are often portrayed as a panacea for the future of health care, but have yet to realize their potential, introducing new practical and ethical challenges. This volume focuses on critical issues surrounding the intersection of genetics, health, and society. It provides a critical examination of sociological and biomedical approaches to genomics, including strengths and limitations of each perspective. It also highlights important epistemological and ethical issues which must be confronted before genomics can be leveraged to improve population health. Furthermore, how genetic technologies and testing have been used in medical practice to date is examined, highlighting the costs and benefits of these innovations to society, groups, and individuals.